Empowering Bhabinkamtibmas in Preventing the Distribution of Drugs in Traditional Communities at Tuban Police - Al Afandi, Arya; Fauzan, Muhammad Shidqy; Iqbal, Mohammad (Akademi Kepolisian Republik Indonesia, 2025)
This final project is compiled based on the importance of the role of Bhabinkamtibmas in preventing drug trafficking in Traditional Communities. The theories used are the Collaborative Leadership theory and the Program Implementation theory. The results of this study show that the Empowerment of Bhabinkamtibmas has never been carried out related to the problem of increasing drug trafficking in Traditional Communities in the Tuban Regency Area. Bhabinkamtibmas has a strategic role as the front guard of the Police to prevent drug trafficking in traditional communities. However, there are still several obstacles to its implementation, such as the lack of coordination between Satnarkoba and Satbinmas regarding the prevention of drug trafficking in Traditional Communities at the Tuban Police. So it is hoped that there will be good vertical and horizontal coordination between the Narcotics Unit and the Binmas Unit owned by the Tuban Police and the Empowerment of Bhabinkamtibmas so that it is appropriately implemented followed by the fulfillment of the needs of the number of Bhabinkamtibmas members themselves.